Effect Extraction of Nigella Sativa and Malricaia chamoilla on Urinary Tract Infection - Hammadi, Amer Ali; Abed, Hadeel Adnan; Rabie, Zahraa Hashim (Scientific Journal of Medical Research, 2021)
Objectives: The proposed of current study determined effectiveness of extracts for Niglle sative and Malricia chamoilla on the Urinary tract infection Bacteria like gram’s positive Staphylococcus aureus, streptococcus faecalis and gram’s negative bacteria Escherichia coli, Klebsiella pneumonia. Methods: For obtain of crude extract of peat solvents had been used are hot, cold water and ethanol , four types of Pathogenic bacteria which tested effectiveness of plant extract and two gram’s positive pathogenic bacteria Staph. aureus, strept. faecalis and gram’s negative bacteria E. coli, K. pneumonia isolated from urinary tract infection (UTI) patient to detection the most active solvent extraction, and used various methods of extraction alcohol, hot water and cold water, then was used of many dilutions to each powder of extraction , to determine the inhibition zone on the plats using well method and measuring the inhibition zone to determine the sensitivity and resistance for UTI infection bacteria. Results: The current study results showed best method of extraction solvent is ethanol that appear through inhibition zone of pathogenic bacteria reach to 50mm in diameter in some case near the inhibition zone of antibiotic diameter. The result also showed there is no effect when used M. chamoilla extract alone on both gram’s negative and positive and there is few effect when used N. sativa extract alone on both gram’s negative and positive but when mixed the plant extraction of both plant N. sativa and M. chamoilla the effect of plant extraction on growth of pathogenic bacteria by diameter of inhibition zone increased reach 50mm, 45mm on gram’s positive bacteria and this result near the inhibition zone of antibiotic while in gram’s negative bacteria reach in range 45mm, 40mm and 35mm diameter of inhibition zone. Result showed there is no effect in cold water extraction. Conclusion: The best method of extraction ethanol extraction and most effectiveness plant extraction when mixed the of N. sativa and M. chamoilla produce antimicrobial activity against gram’s positive bacteria and gram’s negative bacteria when used ethanol extracted method.